2001
DOI: 10.1002/pen.10855
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic simulation of film casting process for a polymer melt

Abstract: Numerical simulations of the film casting process were performed using a finite element method for Newtonian and viscoelasttc fluids. We simplified the governing equations by the assumption that the stress and velocity gradients in the thickness direction were negligible, and obtained the film thickness and mean value of stress and velocity components in the thickness direction as variables. Viscoelasticity was described by the Larson model with multiple relaxation times. Non‐isothermal conditions were conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 9 publications
2
47
0
2
Order By: Relevance
“…5) It was confirmed that the final film shape at the chill roll was not influenced by the boundary conditions at the die exit. 2,3) The die width, die thickness and air gap used in the computations were 250 mm, 0.8 mm and 88 mm, respectively.…”
Section: Governing Equations and Boundary Conditionssupporting
confidence: 59%
See 3 more Smart Citations
“…5) It was confirmed that the final film shape at the chill roll was not influenced by the boundary conditions at the die exit. 2,3) The die width, die thickness and air gap used in the computations were 250 mm, 0.8 mm and 88 mm, respectively.…”
Section: Governing Equations and Boundary Conditionssupporting
confidence: 59%
“…The validity of this assumption has been verified by Satoh et al 5) by comparing the numerical results of fully-three-dimensional simulations. The effect of gravity force can be negligible over 2 in draw ratio.…”
Section: Governing Equations and Boundary Conditionsmentioning
confidence: 55%
See 2 more Smart Citations
“…Interestingly, the level of the strain hardening in uniaxial extensional viscosity is much higher than in the planar extensional viscosity, which is more clearly visible in Figure 5 where normalized uniaxial and planar extensional viscosities are plotted as the function of the extensional strain rate. Recently, it has been revealed [17][18][19][20][21] that the ratio of planar to uniaxial extensional viscosity, Ș E,P /Ș E,U , (i.e. the difference between the strain-hardening nature in planar and uniaxial elongation) controls the level of the unwanted neck-in phenomena (film width reduction occurring during the film casting process between the flat die and the chill/nip rolls) due to the fact that the middle of the film undergoes planar elongation whereas the material at the edge undergoes uniaxial elongation.…”
Section: Resultsmentioning
confidence: 99%